Comparative analysis of differentially expressed genes and transcripts in the ovary of yak in estrus and anestrus - Chongfa Yang; Yahua Yang; Bingzhu Zhao; Enyu Gao; Hao Chen; Yang Li; Junyuan Ma; Jine Wang; Songming Hu; Xiaochen Song; Ying Chen; Gengsacairang Yang; et al. (Animal Biotechnology)
Since most yaks have a long postpartum anestrus period, postpartum anestrus is the main factor affecting the reproductive efficiency of yaks. In this study, the third-generation sequencing technology was used to successfully screen differentially expressed genes (DEGs) and differentially expressed transcripts (DETs) in the ovarian tissues of yaks during estrus and anestrus. The functional references of DEGs and DETs were Gene Ontology, Kyoto Encyclopedia of Genes and Genomes, and Clusters of Orthologous Genes database. A total of 1149 DEGs and 2294 DETs were successfully identified. These DEGs and DETs were mainly related to biological processes such as “reproduction”, “reproductive process”, “metabolic process” and “rhythmic process”. Kisspeptin-G protein-coupled receptor was found to be involved in regulating the reproductive cycle of yaks. DEGs and DETs were also related to gonadotropin-releasing hormone (GnRH) signaling pathways such as oocyte meiosis, estrogen signaling pathway, and progesterone-mediated induced oocyte maturation. The results showed that SIRT1, CSNK1A1, SLIT3, INHBA, INSL3, ZP2, Clock, BMP15, Bmal1, KISS1, and LCHGR regulate the postpartum quiescent state and the reproductive cycle of yaks. This study will help to further clarify the reproductive mechanism of yaks at the molecular level and provide certain assistance for the development of animal husbandry.